The Effects of Inventory Management on the Sales Performance of Logistic Companies in Uganda: A Case Study of Bollore Transport Logistics. - Rhonah Tahinduka (Uganda Christian University, 2023)
The study found out the impact of inventory management on the sales performance of logistic companies in Uganda. The three research objectives that guided the study included examining the impact of inventory turnover on total revenue, identifying the impact of stock out on market penetration and finding out the impact of order cycle time on the lifetime value of a customer. The study employed a cross sectional research design that was descriptive in nature, used to describe characteristics of the population and other phenomenon studied. The researcher also used quantitative data that was analysed using the Statistical Package for the Social Sciences (SPSS) computer program to come up with the findings. that the impact of stock out on market penetration included; stock out has resulted into loss of revenue for a business, Stock outages has decreased customer retention at the company, Out of stock has constantly developed a negative perception to customers about its brand products, Stock out has brought about costs relating to canceled orders and lost customers, Stock outs has lead potential customers to other retailers who will be delighted to immediately fulfill their order, the company has reduced how much it stores to reduce costs and customer reviews have an impact on both acquiring new customers and encouraging repeat custom. The study concluded that, the impact of order cycle time on the lifetime value of a customer included; order cycle time provided us with valuable information about the quality of our supply chain process, knowing the customer order cycle time helped us decide if we are ready to expand operations and reducing customer order cycle time help improve consumer retention. The study recommended that, there is need to detect issues in the supply chain. Knowing the business’s order cycle time help detect issues in the supply chain that could be causing delays in order fulfilment process. A long order cycle time is an indicator that one need to review the supply chain process to identify any inefficiencies or unnecessary steps that need to be optimized or removed entirely. The study was undertaken to find out the impact of inventory management on the sales performance. Data was collected using questionnaires which were based on set objectives that included examining the impact of inventory turnover on total revenue, identifying the impact of stock out on market penetration, and finding out the impact of order cycle time on the lifetime value of a customer. This chapter presents a summary of findings observed and inferred from the data presented in chapter four. The summary of findings is based on the literature available in chapter two. This chapter also provides the conclusions, recommendations and suggested areas for further study.
This is a dissertation